Pengolahan Data Indeks Kepuasan Masyarakat (Ikm) Pada Balai Besar Pengembangan Budidaya Air Tawar (Bbpbat) Sukabumi Dengan Metode Weight Average Index (Wai) - Yanti Nurkhalifah, Iwan Rizal Setiawan , (PROCEEDING IC-ITECHS 2014, 2014)
Community satisfaction index use as a benchmark to assess the level of quality ofservice in the form of a questionnaire which must be done collectively, unified, focused, and consistent as a reference to determine the level of performance of the service unit of government agencies in order to achieve the expected quality. in the use of data processing application CSI is still use evenly, one of them in the center freshwater aquaculture development ( CFAD ) Sukabumi, the application is still not use, the data of the respondents and the data is still conventional CSI. so that by the time the data were collected may appear many errors such as data loss, tucked, or a mistake when entering values. so that the resulting information about agency services to the community are not appropriate. to produce an appropriate and accurate information is required CSI questionnaire data processing application, which use in the data collection phase of the respondents and the CSI data is easily and accurately. the questionnaire data processing can perform processing CSI although the data is still not reached the maximum number specified. the amount of data that has been processed will be displayed on the information in the form of percentage and value of the level of quality of service agencies.